STATUS AND PERSPECTIVES OF DEVELOPMENT OF THE PENSION SYSTEM OF VIETNAM - Manh Hung Tran (Статистика и экономика)
At the present time the pension system of Vietnam like almost of the pension systems in the world confronts many difficulties and challenges. The pension reform in Vietnam should be held in the near future. Its successful implementation requires careful studies of the risks and challenges that undermine the existing pension system in Vietnam. The article reviews the status and the prospects of development of the pension system in Vietnam.